PRINCIPLES OF CREATING EDUCATIONAL SYLLABUS (Ustozlar uchun, 2025)
This article discusses the main principles and stages of designing an effective educational syllabus. The study highlights the importance of defining learning objectives, selecting appropriate content, organizing teaching methods, and aligning assessment with goals. It also emphasizes the role of teachers, learners, and educational standards in the syllabus creation process.